Cancer of the vulva in Burkina Faso: a hospital-based case series. Issue 1 (December 2016) - Zongo, Nayi; Korsaga-Somé, Nina; Banata Gang-Ny, Amandine; Ouangré, Edgar; Zida, Maurice; Ouédraogo, Aimé Sosthène; Bambara, Aboubacar Hirrhum; Bambara, Augustin Tozoula; Traore, Si Simon; Niamba, Pascal; Traoré, Adama; Dem, Ahmadou
Abstract Background Vulvar cancer is a rare gynaecological cancer. In Burkina Faso, the diagnosis of vulvar cancers is delayed and the prognosis is poor. However, no specific study on vulvar cancers has been conducted at the moment. This work aimed to study the characteristics of these cancers. Methods This is a prospective study on histologically confirmed primary cancers of the vulva diagnosed between 1st January 2013 and 30th June 2015. The demographic and clinical aspects were studied at the Yalgado Ouedraogo University Hospital of Ouagadougou (CHU-YO). Results We noticed 21 cases of vulvar cancers within 30 months, ranking it as the 4th most common gynaecological cancer. The average age of the patients was 55 years (standard deviation +/− 6.3) and the median age was 57 years. Scars resulting from female circumcision, menopause (n  = 20) and HIV infection were noticed in 19 cases and 6 cases respectively. The average time from first symptoms to first consultation was 29 months. Pain and ulceration were the main reasons for consultation. The clinical picture was chiefly an ulcero-granulating tumour. There was squamous cell carcinoma in 20 cases and basal carcinoma in 1 case. Fifteen patients were at stage III or IV, where of three patients had metastatic disease. We noticed vitiligo in 9 vulvar cancer cases. Conclusion The cancer of the vulva is rare. Women are of menopausal age, are mostly circumcised and HIV-infection is common. A majority of patients sought consultation at advanced stage of disease, and diagnosis was belatedly made. Pain and ulceration were the main reasons for consultation. The sensitization of the population, education for self- examination would allow earlier diagnosis.